2016
DOI: 10.4995/wrs.2016.3801
|View full text |Cite
|
Sign up to set email alerts
|

Alternative and enriched housing systems for breeding does: a review

Abstract: Abstract:The main results and observations on group and individually housed rabbit does were reviewed by Szendrő and McNitt in 2012, but in recent years several new papers in this field have been published. This provides a new opportunity to summarise the current knowledge on alternative housing systems for breeding does. In Switzerland, rabbit does are generally housed in group systems. The recently legislated Belgian and Dutch housing systems will be converted step by step into group housing systems. Recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 37 publications
0
9
0
1
Order By: Relevance
“…Does housed in C1always remained in the group, and after kindling, they remained with their kits until weaning (30 d). Subsequently, the kits were moved into bicellular cages, and the does were re-inseminated [10] and remained in the same cage until the next kindling (Figure 3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Does housed in C1always remained in the group, and after kindling, they remained with their kits until weaning (30 d). Subsequently, the kits were moved into bicellular cages, and the does were re-inseminated [10] and remained in the same cage until the next kindling (Figure 3).…”
Section: Methodsmentioning
confidence: 99%
“…Hoy and Matics [9] drew the same conclusions; in particular, they affirmed that in the near future, the single housing of does with kits with some enrichment would be the common housing system in intensive rabbit production. Szendrő et al [10], summarizing the advantages and disadvantages of the individual, combined, or grouphousing of does, proposed individual housing, but underlined the necessity of environmental enrichments. Thus, the colony cages proposed for does do not meet the needs of the animals and negatively affect the well-being and the reproductive performance of rabbit does (pseudopregnancy, abortion), and should therefore be modified to be more efficient.…”
Section: Introductionmentioning
confidence: 99%
“…In collective systems, reproductive performance decreases due to high rates of pseudopregnancy (Rommers et al, 2006;Mugnai et al, 2009;Andrist et al, 2013). Moreover, kit mortality is very high because of competition among does for nests, aggressions towards kits and kindling of 2 or 3 does in the same nest box (Mirabito et al, 2005;Hoy and Matics, 2016;Szendrő et al, 2016b;Hoy et al, 2017). Likewise, a very high number of attacks (Szendrő et al, 2016b) and mating attempts between does (Gerencsér et al, 2016) have been observed.…”
Section: Continuous Group-housing In Farmsmentioning
confidence: 99%
“…Moreover, kit mortality is very high because of competition among does for nests, aggressions towards kits and kindling of 2 or 3 does in the same nest box (Mirabito et al, 2005;Hoy and Matics, 2016;Szendrő et al, 2016b;Hoy et al, 2017). Likewise, a very high number of attacks (Szendrő et al, 2016b) and mating attempts between does (Gerencsér et al, 2016) have been observed. Decreased sanitary status, higher culling and shorter lifespan have also been reported (Andrist et al, 2013;Szendrő et al, 2013) (Table 3).…”
Section: Continuous Group-housing In Farmsmentioning
confidence: 99%
“…Para conseguir este agrupamiento temporal, se favorece o se impide el contac to entre las hembras mediante paredes móviles en las jaulas, o mediante puertas que puedan cerrarse o abrirse, permitiendo la formación del grupo o la individualización de las reproductoras a juicio del cuidador. No obstante, sea cual sea el protocolo, la agresividad y las lesiones consecuentes al restablecimiento de la jerarquía (Buijs et al, 2015) así como el estrés, me dido en función de la evolución de la tempe ratura corporal (Graf et al, 2011; Andrist et al, 2014) (Figura 1) y del nivel de glucocorticoides (Szendrö et al, 2016;Ródenas et al, 2019), se reactivan cada vez que las hembras vuelven a reunirse. Estas manifestaciones negativas son especialmente frecuentes en las conejas más jóvenes (Róde nas et al, 2019) y también cuan do los grupos no son estables porque se incor pora reposición (Andrist et al, 2012).…”
Section: Manejo De Las Reproductoras En Grupounclassified